Edukasi Hidup Sehat Tanpa Diabetes Dengan Pemanfaatan Tanaman Obat Bagi Masyarakat Desa Mekarjaya Banjaran - Ida Musfiroh; Sandra Megantara; Holis Abdul Holik; Yasmiwar Susilawati; Gofarana Wilar (Journal of Community Development, 2023)
Diabetes mellitus in Indonesia now ranks 5th with the highest number of diabetes mellitus sufferers in the world. At present, the prevalence has increased from 6.2% compared to 2019. Diabetics need to get effective and safe drugs in order to avoid various complications. In addition to using pharmacological therapy, it is also necessary to carry out non-pharmacological therapy. One type of medicinal plant that is known to be effective in reducing sugar is ginger and cinnamon, but there has not been much reported on its processing other than in the form of a decoction or marinade. The purpose of carrying out this PPM activity is to increase the knowledge and understanding of the people of Mekarjaya Banjaran Village regarding the use of medicinal plants as anti-diabetics, and provide knowledge about making ginger-cinnamon instant powder drinks. The activity method is carried out in 3 stages, namely the planning, implementation, evaluation and follow-up stages. The results of this PPM activity show that the community has a better understanding of efforts to be healthy in preventing diabetes through the use of ginger-cinnamon medicinal plants, and how to process them through instant powders. The evaluation is carried out based on the results of the initial test and the final test as a method for measuring the achievements of this PPM activity.